INTEGRATION OF THE KYRGYZ REPUBLIC INTO GLOBAL VALUE CHAINS: EXPORT STRUCTURE, OPPORTUNITIES, AND CONSTRAINTS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article analyzes the current state of the Kyrgyz Republic’s export economy in the context of the country’s participation in global value chains (GVCs). Relevant statistical data on the structure and dynamics of Kyrgyzstan’s exports are presented, based on materials from the National Statistical Committee of the Kyrgyz Republic and international databases. The key export sectors are identified: primarily the mining industry (gold and precious metals), as well as raw fuel resources. The leading export markets are Switzerland (28–32% of total exports) and the EAEU countries. It is shown that only about one-third (≈32%) of Kyrgyzstan’s foreign trade is linked to participation in GVCs, with a dominant raw-material component (mainly “backward” integration). The article examines internal factors constraining integration, including dependence on raw materials, a poorly diversified economy, geographical remoteness and infrastructural issues, as well as institutional barriers such as complex customs procedures and excessive bureaucracy. The study evaluates opportunities to enhance export potential through GVCs — entering new markets, industrializing the processing sector, and developing cluster projects (in textiles, food industry, electronics, and deeply processed agricultural products). Recommendations are formulated to increase the added value of exported raw materials (for example, local metal processing and jewelry production), to develop logistics infrastructure, to improve the business climate, and to utilize the mechanisms of the EAEU and international agreements to deepen integration into global value chains.
Keywords: global value chains; export potential; export structure; added value; economic diversification; raw material dependence; infrastructural constraints; institutional barriers; industrialization; cluster approach.